Pilot scale hydrodynamic cavitation and hot-water extraction of Norway spruce bark yield antimicrobial and polyphenol-rich fractions - Tienaho, Jenni; Liimatainen, Jaana; Myllymäki, Laura; Kaipanen, Kalle; Tagliavento, Luca; Ruuttunen, Kyösti; Rudolfsson, Magnus; Karonen, Maarit; Marjomäki, Varpu; Hagerman, Ann E.; Jyske, Tuula; Meneguzzo, Francesco; et al. (Elsevier BV, 2025)
Norway spruce (Picea abies [L.] Karst) tree bark contains high concentrations of polyphenolic compounds with antibacterial, antioxidant, and antiviral properties. While laboratory-scale extraction studies are relatively abundant, the behavior of biomass properties and compound profiles during upscaled processing have remained underexplored. This study addresses the gap by assessing the industrial feasibility of using an industrial-scale assortment of bark biomass obtained directly from a sawmill. It compares two green pilot-scale extraction methods using only water as the solvent: hydrodynamic cavitation and hot-water extraction. The resulting lyophilized and spray-dried extracts were analyzed for their antibacterial, antiviral, and antioxidant activities, as well as their chemical composition, including carbohydrate, stilbene, tannin, and terpene contents. To further evaluate the industrial potential, a technical feasibility analysis was conducted, highlighting material and energy balances for both extraction processes and identifying areas for improvement. The findings indicate that both extraction methods effectively yielded polyphenol-rich extracts with desirable bioactivities. Notably, hot-water extracts, with slightly higher condensed tannin and stilbene content, exhibited higher antioxidant activity and greater efficacy against enterovirus (coxsackievirus A9), while hydrodynamic cavitation products showed higher activity against gram-positive and gram-negative bacteria. Lyophilization resulted in slightly lower chain-length, but higher concentrations of tannins and stilbenes compared to spray-drying. Overall, this study demonstrates that upscaled processing of spruce bark can effectively and sustainably produce commercially viable extraction products.